THE IMPACT OF CLIMATIC CONDITIONS ON THE FEATURES AND COURSE OF BRONCHIAL ASTHMA WITH CONCURRENT ALLERGIC DISEASES - Salibayeva N. O.; Yuldashev I. R. (Journals Park Publishing, 2024)
Bronchial asthma is a chronic inflammatory disorder of the airways that often coexists with other allergic diseases. The clinical manifestations and disease course of asthma can be significantly influenced by the climatic conditions of the region. This study aimed to investigate the features and progression of bronchial asthma in combination with other allergic diseases, with a particular focus on the impact of climatic factors.
Keywords: Bronchial asthma, Allergic diseases, Climatic conditions, Temperate climate, Subtropical climate, Subarctic climate, Asthma symptoms, Lung function, Biomarkers, Allergic comorbidities, Environmental factors.